Occurrence of oxidative stress in dairy cows seropositives for Brucella abortus - Perin G.* (2017)
© 2017 Elsevier LtdBovine brucellosis is an important zoonotic disease caused by the bacterium Brucella abortus that leads to economic losses due to animal discard and commercial restrictions. Since positive animals for brucellosis are culled, little is known about the pathogenesis of this disease. Therefore, the aims of this study were to evaluate possible changes in the activity of deaminase adenosine (ADA) and the oxidative stress in cows seropositives for brucellosis (Experiment I), and to evaluate the seroprevalence of B. abortus in dairy cows from the Western state of Santa Catarina, Southern Brazil (Experiment II). The Experiment I evaluated 20 pregnant cows: ten seropositives for B. abortus and ten seronegatives that were used as controls. The ADA activity and markers of oxidative stress (TBARS, catalase (CAT) and superoxide dismutase (SOD)) were evaluated in these animals. A reduction in the activity of ADA and catalase enzymes in seropositive animals was observed (p < 0.001). Conversely, there was an increase in TBARS levels and superoxide dismutase activity in cows infected by B. abortus (p < 0.001). The presence of oxidative stress and a reduction of ADA might be related to the modulation of the inflammatory response. The experiment II was performed due to a high number of herds with restrictions imposed by cases of brucellosis in the state of Santa Catarina in the last two years, and thus, the seroprevalence for B. abortus was evaluated in 1242 serum samples of cows of 69 herds. The serodiagnosis was performed using two tests: buffered acidified antigen and 2-mercaptoethanol. However, none of the serum samples were positive for B. abortus. Although we did not find seropositive animals for brucellosis in our study, the disease still requires continued surveillance, due to its economic impact, and to the oxidative stress caused by it, which may have contributed to cases of abortion in three seropositive cows (Experiment I) in the final third of the gestation.